Laser deposition of aluminum and magnesium‑based alloys for repair and surface restoration of components - B. M. Nemenenok; O. G. Devoyno; P. E. Lushchik; I. V. Rafalski; A. D., Rulenkov (Литьë и металлургия)
The results of studying the processes of laser deposition of aluminum and magnesium‑based alloys, the features of the structure of deposited layers using electron microscopy and X‑ray computed tomography data, measurements of microhardness after laser deposition of aluminum and magnesium alloys are presented. Modeling of the stress‑strain state of flat components during laser deposition of an aluminum‑magnesium alloy containing 0.6–0.95 % magnesium, 0.7–1.0 silicon, up to 0.3 titanium, up to 0.5 zinc, and up to 0.4 % manganese was performed. The nature of the distribution of deformations and stresses during the use of various technological schemes of laser deposition during surface treatment of aluminum‑magnesium alloys by laser deposition methods is established.